Screening of Brewery Yeast Strains Regarding Organic Acid Profile in Order to Find Low Succinic Acid Producer - Tyrell, thomas; Reimann, Stefan; Folz, Roland; Harms, Diedrich; Hinrichs, Johannes; Offer, Guido (BrewingScience, 2013)
The yeast collection of VLB Berlin provides with more than 80 strains a broad range of top and bottom fermenting yeasts for the use in beer and wine production. As organic acids in alcoholic fermentation become more and more of interest regarding health and drinkability [1, 2, 3, 4, 5, 6], a screening was carried out to select strains with a reduced production rate of succinic acid. It was possible to show, that with the right selection of yeast, beer with considerable lower amount of succinic acid can be produced. Additionally this work gives an overview on yeast strain impact on other organic acids. Furthermore scale-up conditions between laboratory and pilot scale fermentations are discussed.